SOLUTION OF PARTIAL DIFFERENTIAL EQUATIONS BY ELZAKI TRANSFORM - DEVI, ANJU; JAKHAR, MANJEET; GILL*, VINOD (International Journal of Mathematical Archive, 2018)
In this paper, we introduce a computational algorithm for solving partial differential equations such as Heat Equation, Wave Equation, Laplace Equation and Telegrapher’s Equation etc. by using the modified versions of Laplace and Sumudu transforms which is called Elzaki transform. The Elzaki transform, whose fundamental properties are presented in this paper. Illustrative examples are presented to illustrate the effectiveness of its applicability.